Computational simulation of dispersion of a compressible medium emitted by a local source - Boyarshinov, Mikhail Gennad'evich; Balabanov, Denis Sergeevich (Computational Continuum Mechanics, 2010)
Mathematical simulation of the dispersion of an ideal compressible gas emitted by a local source is considered. The Euler system of differential equations (continuity, impulse, energy and state) and the appropriate initial and boundary conditions are used. The numerical solution is based on the method of large particles (Davydov's method). The exact solution of the problem is used to verify the obtained numerical solution. For improving the accuracy of the numerical solution, the shape of the local source is approximated by elementary cells.
Keywords: gas dynamics; Euler system of equations; ideal gas; local source; method of large particles